ANXIETY AMONG SCHOOL-AGE CHILDREN IN WAR-AFFECTED AREAS IN UKRAINE AND WAYS TO REDUCE IT: PARENTS’ VIEWS - Malykhin, Oleksandr; Kaupuzs, Aivars; Aristova, Nataliia; Orska, Rita; Kalvans, Eriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The Ukrainian-Latvian team of researchers are dedicated to commit their research to finding out parents’ views on whether school-age children experience anxiety in war-affected areas in Ukraine and ways to reduce it. The research also enables to identify the most common signs of anxiety. The data collection instrument includes a web-based questionnaire developed by researchers from Ukraine using Google Forms. All researchers are involved in sharing the developed web-based questionnaire via social media networks. The research sample includes 1346 parents of school-age children from all the parts of Ukraine, namely, Central, Eastern, Western, Northern, Southern Ukraine and Kyiv. Research findings demonstrate the urgent need to implement targeted psychological and pedagogical influences (the use of technologies, methods and techniques aimed at reducing the level of anxiety in school-aged children) in the educational process of general secondary schools, regardless of whether this process is carried out face-to-face, remotely or in a blended learning format. The conducted research makes it possible to substantiate the necessity of creating a web-based support system for educators to reduce anxiety among school-age children. The current research is carried out within the project “Web-based Support System for Educators to Reduce Children’s Anxiety in War-affected Areas” (Registration No GPK-07/2022).